Efektivitas Pemberian IAA, IBA, NAA, dan Root-up pada Pembibitan Kesemek - Setiawan, Eko (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACTOriental persimmon (Diospyros kaki L.) originated from and has mainly been cultivated in China, Korea, and Japan, and currently it is cultivated in Batu, Kuningan, and Brastagi regions, Indonesia. Success in propagating persimmon in Indonesia has been limited. The objective of the study was to determine propagation techniques through root cutting supplemented with auxin treatment. All seedlings from root stock cutting supplemented with 100 ppm of either indoleacetic acid (IAA), indolebutyric acid (IBA), α-napthaleneacetic acid (NAA), or Root-up, and control. The results showed bud form stem or root cuttings treated with IAA, NAA and Root-up 100 ppm emerged earlier than IBA 100 ppm and control. The percentage of mortality of Root-up 100 ppm treatment and control cuttings was the highest (50%) than the others treatments. IAA and IBA treatments stimulated larger number of shoot, 16.5 and 17.0 shoots, respectively. The number of leaves was higher in plant treated with IAA 100 ppm (20.8 leaves). Keywords: auxin, Diospyros kaki L., germination, leaf number, root stock ABSTRAK Tanaman kesemek atau oriental persimmon (Diospyros kaki L.) banyak dibudidayakan di China, Korea, serta Jepang, dan saat ini banyak ditanam di Indonesia seperti di daerah Batu, Kuningan, dan Brastagi. Keberhasilan pembibitan kesemek di Indonesia masih rendah. Penelitian bertujuan untuk memperbanyak tanaman secara vegetatif dari pemisahan tunas akar dengan perlakuan auksin guna mendukung pengembangan pembibitan tanaman kesemek. Perbanyakan tanaman dilakukan dengan tunas akar yang direndam dengan auksin (IAA, IBA, NAA, dan Root-up; masing-masing 100 ppm), serta perlakuan kontrol. Hasil penelitian menunjukkan perlakuan IAA, NAA dan Root-up 100 ppm menghasilkan tunas lebih awal dibandingkan dengan kontrol dan IBA 100 ppm. Tingkat kematian bibit tertinggi mencapai 50% terjadi pada perlakuan Root-up 100 ppm dan kontrol. Jumlah tunas terbanyak dihasilkan oleh perlakuan IAA dan IBA sebanyak 16.5 dan 17.0 tunas. Jumlah daun terbanyak dihasilkan oleh perlakuan IAA 100 ppm (20.8 helai).Kata kunci: auksin, Diospyros kaki L., jumlah daun, muncul tunas, tunas akar